METODE PEMASARAN ON LINE UNTUK MENINGKATKAN PENJUALAN EKSPOR ROTAN DI DESA TRANGSAN GATAK SUKOHARJO - Suranta, Sri; Sulardi, Sulardi; Syafiqurrahman, Muhammad (LPPM Universitas Pamulang, 2020)
The purpose of community service carried out by the UNS Team was to assist Small and Medium Enterprises (SME), especially Wayan Rotan SME and Tiga Warna Rotan SME in order to increase the sale of rattan products to exports. The problem faced by the two SMEs is the sale of rattan products that have not been optimal because the marketing methods carried out are still conventional. The methods used in implementing this activity are: the procurement of online marketing facilities, including notebooks, and modems, making websites as a means of online marketing, and conducting training related to online marketing. The result of service that has been done is increasing sales of rattan products by 38%.